PERILAKU KONSUMEN PENIKMAT KOPI TUBRUK DAN KOPI INSTAN - Sudiyarto Sudiyarto; Sri Widayanti; Dya Maretya Kresna (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2012)
The levels of Indonesian domestic coffee consumption increases more and more; this is related to consumer behavior, living standards improvement and lifestyle shift of urban people as in Surabaya. Each year coffee processing industry continues to grow in line with market demand. The purpose of this study was to: 1) describe the type of product and the known and favored coffee brand, 2) analyze consumer behavior in purchasing or consuming mud coffee and instant coffee. The research was conducted in Surabaya in March-April, 2012. This research applied qualitative-descriptive analysis. The coffee brand available in all traditional stores and minimarkets was only one brand of coffee (Kapal Api brand), while the coffee brands which were available in minimarket but were not available in traditional stores/food stalls were 4 brands of coffee. The coffee lovers bought coffee mostly in food stalls. Further, consumers enjoyed coffee at home, while the type of coffee mostly chosen was in form of original coffee powder, and the time to enjoy coffee was most frequently at night. Consumers enjoyed coffee for 2 cups/day in average. The consumer considerations in choosing coffee were influenced by flavor and external factors, mostly due to friendship effect. 55.00 percent of consumers preferred mud coffee. Keywords: consumer behavior, coffee, type (mud, instant) and brand.